On the estimation of intracluster correlation for time‐to‐event outcomes in cluster randomized trials. (27th October 2016) - Kalia, Sumeet; Klar, Neil; Donner, Allan
Abstract : Cluster randomized trials (CRTs) involve the random assignment of intact social units rather than independent subjects to intervention groups. Time‐to‐event outcomes often are endpoints in CRTs. Analyses of such data need to account for the correlation among cluster members. The intracluster correlation coefficient (ICC) is used to assess the similarity among binary and continuous outcomes that belong to the same cluster. However, estimating the ICC in CRTs with time‐to‐event outcomes is a challenge because of the presence of censored observations. The literature suggests that the ICC may be estimated using either censoring indicators or observed event times. A simulation study explores the effect of administrative censoring on estimating the ICC. Results show that ICC estimators derived from censoring indicators or observed event times are negatively biased. Analytic work further supports these results. Observed event times are preferred to estimate the ICC under minimum frequency of administrative censoring. To our knowledge, the existing literature provides no practical guidance on the estimation of ICC when substantial amount of administrative censoring is present. The results from this study corroborate the need for further methodological research on estimating the ICC for correlated time‐to‐event outcomes. Copyright © 2016 John Wiley & Sons, Ltd.